Identifying Items for “Self-Reflection” as a Religious Factor to Succeed in the Pre-Sea Training - Mohd Noor, Ahmad Firdaus Bin; A Shukor, Khairunnisa Binti; Zainal Abidin, Mohd Zahirwan Halim; Abd Razak, Muhd Imran; Hassan, Paiz; Abd Basir, Mukhamad Khafiz (Jurnal Ilmiah Peuradeun, 2022)
Self-reflection has become a necessary skill to achieve the goal students set for themselves to be successful in pre-sea training. It helps students to improve their actions in critical situations, primarily when supported by religious practices. This study aimed to identify items that represent self-reflection as a religious factor for success in pre-sea training. A three-round Delphi approach was adopted in which ten experts were selected who met the necessary condition to participate in the study. Data were analyzed quantitatively using SPSS version 23 for median and IQR. The study found that self-reflection can be implemented through meditation and self-evaluation, the act of repentance, and returning to the source of religion. However, the experts felt that isolation is unsuitable for them as a ship's crew. They are advised to find other methods of meditation and self-assessment, such as self-contemplation. Students should return to the sources of religion, including the Quran and Sunnah, by reading books and online references and also seek the help of knowledgeable and pious people. However, experts pointed out how difficult it is for a Muslim to reach out to this pious person when he is the only Muslim on board. This study has developed 18 practices for students to implement self-reflection in the form of meditation and self-contemplation.